2010
DOI: 10.1016/j.ijantimicag.2009.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Acute uncomplicated cystitis: from surveillance data to a rationale for empirical treatment

Abstract: The objectives of this study were to explore the epidemiological features and resistance rates in uropathogens isolated from cases of acute uncomplicated cystitis (AUC) in Greece, and subsequently to guide empirical treatment. Urine samples from outpatients aged >16 years were cultured and for each uropathogen isolated non-susceptibility to orally administered antimicrobial agents was defined. Demographic and clinical data were provided in questionnaire form. From January 2005 to March 2006 a total of 1936 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
2
27
1
Order By: Relevance
“…Both studies showed susceptibility rates in excess of 95% for three antimicrobials (fosfomycin, nitrofurantoin and mecillinam) and a significant degree of resistance to ampicillin, SXT and the fluoroquinolones. The degree of antimicrobial resistance observed in E. coli in the current study is also comparable with that reported recently by others in the UK (comparable ampicillin and trimethoprim resistance rates) [23], the Iberian peninsula (high resistance to ampicillin and SXT and low resistance to nitrofurantoin, cephalosporins and fosfomycin) [24] and Greece [25].…”
Section: Multiple Resistance Profile Eco·sens I Eco·sens Iisupporting
confidence: 91%
“…Both studies showed susceptibility rates in excess of 95% for three antimicrobials (fosfomycin, nitrofurantoin and mecillinam) and a significant degree of resistance to ampicillin, SXT and the fluoroquinolones. The degree of antimicrobial resistance observed in E. coli in the current study is also comparable with that reported recently by others in the UK (comparable ampicillin and trimethoprim resistance rates) [23], the Iberian peninsula (high resistance to ampicillin and SXT and low resistance to nitrofurantoin, cephalosporins and fosfomycin) [24] and Greece [25].…”
Section: Multiple Resistance Profile Eco·sens I Eco·sens Iisupporting
confidence: 91%
“…for example, in contrast to our approximately 18% prevalence of fQs resistance in E. coli, the European Eco sEns study, which involved 2,478 E. coli urinary isolates from 252 community health care centers in 17 countries (early 2000s), found approximately 2% ciprofloxacin resistance. 14,15 Likewise, a Greek study of 1,936 E. coli uncomplicated cystitis isolates (January, 2005 to March, 2006) found < 5% ciprofloxacin resistance, 16 whereas, as noted above, a London study from 2005-2006 showed 9.3% fQs resistance among E. coli from the local community (including some hospitalized patients). Whether our markedly higher resistance prevalence reflects differences in geography, time period, patient selection, or other factors is unknown.…”
Section: Number Of Isolates (Column %)mentioning
confidence: 95%
“…Some authorities even suggested continuing the use of TMP-SMX even if resistance rates are 30% or higher, in light of the benign, self-limited course of uncomplicated UTI and given the threat of emerging quinolone resistance (12,16,20,28,34,35,38). However, prescribing practices suggest that current guidelines are often not followed and that use of quinolones in UTI is in fact increasing (3,11,22,23,33,42). Given the documented correlation between antibiotic use and resistance rate, this is likely to increase the problem of quinolone-resistant pathogens (9).…”
mentioning
confidence: 99%